Best practice of green island resorts - Yusof, Zeenat Begam; Jamaludin, Mariam (Elsevier, 2013)
Hospitality industry development is the core facilities in the tourism industry. The issues sustainability and green are discussed when looking at the effort by the resorts operators at practicing green approaches. The objective of this study was to find out the best practice and the factors influence the best practice of the resort operators. The research method employed was structured observation, documents analysis and in depth interview. The findings show that, green initiatives help to cut down the running cost and each resorts adopts different best practice that suit their operation and environment.